HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN MOMTONG DOLLYO CHAGI TIM PUTRA DOJANG GARUDA FIGHTER PEKANBARU - Mutiara Zulmi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is the speed of the Momtong Dolly Chagi kick is still less than optimal. The kick done by the athlete looks underpowered so that the opponent is easy to deflect it. Only a few athletes are able to attack with a momtong Dolly Chagi kick that matches the criteria point. The speed of the kick at the time of the momtong dollyo chagi kick is different between the athletes. Coordination of movements that are less dynamic can also be seen from the rigidity of the athlete's attitude when kicking. The purpose of this study was to determine the relationship between leg muscle power and momtong dollyo chagi kick speed at the Putra Dojang Garuda Fighter Pekanbaru Team. The population and sample in this study were participants of the Pekanbaru Dojang Garuda Fighter Team, the total number of students was 8 students. The instruments used to collect data were leg muscle power tests with vertical jump tests and momtong dollyo chagi kick tests. The data analysis technique used is the test r. Based on the calculation results, it can be seen that there is a relationship between leg muscle power and the ability of the momtong dollyo kick, the Putra Dojang Garuda Fighter Pekanbaru Team, which is found to be calculated = 0.811. At a significant level of 5%, rtable = 0.754 was found. thus r count> r table or 0.811> 0.754.Key Words: Leg Muscle Power, Momtong Dollyo Chagi Kick